Pengaruh Kepercayaan, Keamanan, dan Persepsi Resiko terhadap Keputusan Pembelian Online pada Marketplace Lazada - Ardialis, M. Bobby; Hayani, Nurrahmi (Indonesian Journal of Business Economics and Management, 2022)
This study aims to determine the effect of trust, security, and perceived risk on online purchasing decisions at Lazada by the people of Pekanbaru. This study uses primary data obtained through distributing questionnaires and documentation. The sample selection method is purposive sampling and uses SPSS version 22. Data analysis uses multiple linear regression analysis tools and the classic assumption test consisting of normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. Hypothesis testing is done by t testing, f testing and determination (R2). Based on the results of data analysis, it shows that partially trust, security, and perceived risk have a positive and significant effect on online purchasing decisions. While simultaneously the three independent variables together have a positive and significant effect on the purchasing decision process. The contribution value is 62%. This shows that trust, security, and perceived risk have an influence of 62% on the online purchasing decision process at Lazada and the remaining 38% is explained by other variables that were not examined in this study.